Legal regime of business partnership property (considering international experience) - R. M. Artemenko (Law and Safety, 2023)
The article concludes that property as a special object is a separate thing, a set of things, as well as property rights and obligations. This understanding, despite the existence of certain terminological differences, coincides with its general understanding in the system of legal knowledge of certain countries of the Romano-Germanic legal family, in particular, countries with a pact system of law, and corresponds to the content of Article 1 of Protocol 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms. In the legal literature, it includes any economic benefits, objects of both the material and intangible world, which are in the state of appropriation of a person. At the same time, the word “property”, as used in Article 1 of Protocol 1 to the Convention, refers to an object of economic value. In this sense, property is an economic category and synonymous with the economic concept of “ownership”. This is also indicated by the use of such concepts as “assets”, “funds”, “profit”, “goodwill”, “accumulated intangible assets of the enterprise”, “property of economic value” in the ECHR judgments to describe the category of property.